2003年から11年間のアイスランドと日本の大気中宇宙線生成核種 Be-7濃度変動と太陽活動 - 櫻井, 敬久; 紅林, 泰; 菊地, 聡; 乾, 恵美子; 増田, 公明; 門倉, 昭; 佐藤, 夏雄; B. Gunnlaugur; Sakurai, Hirohisa; Kurebayashi, Yasushi; Kikuchi, Satoshi; Inui , Emiko; et al. (2014)
conference object